One-pot ligation-oxidative deselenization at selenocysteine and selenocystine - Payne, Richard J.; Mitchell, Nicholas J.; Kulkarni, Sameer S.; Wang, Siyao; Malins, Lara (Wiley, 2017)
The use of native chemical ligation at selenocysteine (Sec) with peptide thioesters and additive-free selenocystine ligation with peptides bearing phenyl selenoesters, in concert with one-pot oxidative deselenization chemistry, is described. These approaches provide a simple and rapid method for accessing native peptides with serine in place of Sec at the ligation junction. The efficiency of both variants of the one-pot ligation-oxidative deselenization chemistry is probed through the synthesis of a MUC5AC-derived glycopeptide.